Major Outer Membrane Protein Omp25 of Brucella suis Is Involved in Inhibition of Tumor Necrosis Factor Alpha Production during Infection of Human Macrophages - Jubier-Maurin, Véronique (American Society for Microbiology, 2001)
Brucella spp. can establish themselves and cause disease in humans and animals. The mechanisms by which Brucella spp. evade the antibacterial defenses of their host, however, remain largely unknown. We have previously reported that live brucellae failed to induce tumor necrosis factor alpha (TNF-α) production upon human macrophage infection. This inhibition is associated with a nonidentified protein that is released into culture medium. Outer membrane proteins (OMPs) of gram-negative bacteria have been shown to modulate macrophage functions, including cytokine production. Thus, we have analyzed the effects of two major OMPs (Omp25 and Omp31) of Brucella suis 1330 (wild-type [WT] B. suis) on TNF-α production. For this purpose, omp25 and omp31 null mutants of B. suis (Δomp25 B. suis and Δomp31 B. suis, respectively) were constructed and analyzed for the ability to activate human macrophages to secrete TNF-α. We showed that, in contrast to WT B. suis or Δomp31 B. suis, Δomp25 B. suis induced TNF-α production when phagocytosed by human macrophages. The complementation of Δomp25 B. suis with WT omp25 (Δomp25-omp25 B. suis mutant) significantly reversed this effect: Δomp25-omp25 B. suis-infected macrophages secreted significantly less TNF-α than did macrophages infected with the Δomp25 B. suis mutant. Furthermore, pretreatment of WT B. suis with an anti-Omp25 monoclonal antibody directed against an epitope exposed at the surface of the bacteria resulted in substancial TNF-α production during macrophage infection. These observations demonstrated that Omp25 of B. suis is involved in the negative regulation of TNF-α production upon infection of human macrophages.